Forensic Science (United States : Larsen and Keller Education, 2018)
Forensic science refers to the field of science which is used in criminal investigations to analyze, preserve and collect evidence from the investigation scene. Some of the procedures used in solving crimes using forensic science are toxicology, fingerprint reports, DNA identification, anthropometry, etc. There are many sub-branches of forensic science such as digital forensics, computational forensics, forensic anthropology, forensic botany, forensic chemistry, forensic limnology, etc. Different approaches, evaluations and methodologies and advanced studies on forensic science have been included in this book. It provides deep information about the various concepts and theories related to this field. It is an essential guide for both academicians and those who wish to pursue this discipline further.
Includes index.
Includes bibliographical references.
Keywords: Medical jurisprudence; Nuclear activation analysis; Medical jurisprudence; Criminal investigation; Forensic ballistics; Chemistry, Forensic